EXPANSION OF LOCAL BUDGET REVENUE BASE IN UZBEKISTAN - Fayziev, Farrukh (International Conference on Business & Management, 2026)
This article examines real estate taxation, its specific features, scholars who have conducted research in this area, the legal basis for real estate taxation, the proposed methodology for indexing cadastral value, approaches to cadastral valuation in real estate taxation, and the experience of foreign countries in establishing real estate tax rates.